PEMBELAJARAN NARASI MENGGUNAKAN PENDEKATAN SAINTIFIK DI KELAS VII SMPN 20 KOTA SINGKAWANG - Martono, Martono; Tri Handayani, Natalia Hesty (Universitas Tanjungpura, 2024)
The scientific learning approach is a learning process designed by teachers so that students are active in constructing procedures and principles through the steps of a scientific approach. The research looked at the implementation of narrative learning using a scientific approach at SMPN 20 Singkawang including: planning, implementation, and learning outcomes for writing narratives. Qualitative descriptive research method. Data collection techniques: observation, interviews, and documents. Research results: (a) lesson planning for first meeting 8.17, second meeting 8.20 (b) implementation of learning for first meeting 8.50, implementation of learning for second meeting 8.60, (c) learning outcomes: KD 3.3= 88.5; KD 4.3=82.5